Konseling Indigenous: Menggali Nilaiâ€“Nilai Kearifan Lokal Tradisi Sedekah Bumi dalam Budaya Jawa - Suci Prasasti (Cendekia: Jurnal Pendidikan dan Pembelajaran)
One of the traditions of the Javanese people that still exists today and is ingrained and has become a routine for the Javanese every year is â€˜sedekah bumiâ€™. The systematic literature review (SLR) approach is used in this paper to examine five scientific articles on the local wisdom values â€‹â€‹of the â€œsedekah bumiâ€ tradition (Indigenous Counseling) practiced in Javanese culture. For Javanese people who work as farmers and fishermen, this tradition has become an annual ritual. â€˜Sedekah bumiâ€™ or â€˜sedekah lautâ€™ tradition is not only a routine that is carried out every year, but both traditions have deep meaning and are ingrained in Javanese society. Therefore, even now the Javanese people still carry out the tradition of â€œsedekah bumiâ€and â€˜sedekah lautâ€™ and make it their identity in their daily behavior. â€˜Sedekah bumiâ€™ tradition is carried out once a year in order to maintain harmonious relations between individuals and their ancestors or with nature and is a form of local wisdom in the form of ceremonies or traditions which are a manifestation of communication between humans and nature.